Pedagogy as the Core of Education: Implementing Knowledge, Ethics, and Professional Boundaries in Teaching Practice - Fatema Miah (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
Education is the fundamental embedded aspect in life. Pedagogy what is the deep rooted core concept in the field of education and it is a broader subject of discussion, and an embedded aspect what is implemented in education. Pedagogy, term in education is an implementation of knowledge for learning to teaching or for the educators to be able to put the leaning in practice, to be able to practise their leaning skills and knowledge in teaching or in managing learning and while facilitating the learning to learners or to be able to practise accurately in handling and managing, delivering the sessions or services or maintaining the conducts, in contacts. Verily, the contact is a very sensitive matter in all aspects aware is needed, and respect and decency isessential to be maintained. At most services or practises there is precautionary orders in placed or mandates are instructed, while there maintained boundaries of essential safe guarding.